O‐Health‐Edu: A vision for oral health professional education in Europe. (6th June 2022) - Field, James; Dixon, Jonathan; Davies, Julia; Quinn, Barry; Murphy, Denis; Vital, Sibylle; Paganelli, Corrado; Akota, Ilze; Gerber, Gabor; Roger‐Leroi, Valerie; Manzanares‐Cespedes, Maria Cristina; Tubert‐Jeannin, Stephanie
Abstract: This consensus paper reports on the process of developing a renewed vision for Oral Health Professional (OHP) education across Europe, and forms part of a larger EU‐funded collaborative Erasmus+ project, "O‐Health‐Edu." The vision aligns with the World Health Organisation milestones (2016) and resolutions (2021), and EU4Health programme (2020) objectives ‐ and projects 20 years into the future, to 2040. This longitudinal vision takes a multi‐stakeholder perspective to deliver OHP education that acts in the best interests of both students and patients, and sits within the context of a wider strategy for general health. Included, it is an infographic to help communicate the vision to various stakeholders of OHP education.